Differential responses of a benthic meiofaunal community to an artificial oil spill in the intertidal zone. (March 2014) - Kang, Teawook; Min, Won-Gi; Rho, Hyun Soo; Park, Heung-Sik; Kim, Dongsung
<x content-type="archive" xml:space="preserve">Abstract</x> This study aimed to determine the potential impact of an oil spill on intertidal meiofauna at a clean, sandy beach in Korea. This objective was accomplished by examining changes in the structure of meiofaunal assemblages after a controlled oil spill of different concentrations on the beach. The concentration of total petroleum hydrocabon (TPH) in the experimental plots after oil application was expectedly higher for the first 4 d compared to before oil application. The TPH concentrations decreased at a faster rate in the first 4 d, and then progressively. The sharp decline in meiofaunal density in the experimental plots during the first 4 d after the spill might be attributed to the short-term toxic effects of the oil. This suggestion is supported by a significant negative interaction of the TPH on meiofaunal density during the study period. The period of low density of meiofauna also coincided with the maximum concentration of TPH in the sediment. The multivariate indices proved to be highly efficient, showing that samples contaminated with oil had high TPH concentrations, and were partially separated in terms of meiofaunal communities from samples before oil application or samples with low TPH concentrations. The structure of the meiofaunal communities in the experimental plots was similar before and 1 month after oil application. However, the density of meiofauna sharply decreased immediately after oil application in the experiment plots. Furthermore, the meiofaunal density recovered slowly as time passed.